Zakat, Wakaf, dan Stabilitas Moneter: Perspektif Ekonomi Islam untuk Masa Depan Berkelanjutan - Evi Noor Aliyah; Rezkie Amalia; Muhammad Ibnu Nazar; Muhammad Haris Fadilah; Erwan Setyanoor (PT. Pustaka Andil Lestari, 2025)
Zakat and waqf are two fundamental pillars in Islamic economics, both of which play a strategic role in promoting social welfare and economic stability. This study explores the contribution of zakat and waqf to monetary stability from an Islamic economic perspective, aiming to support sustainable development in Indonesia. Employing a qualitative library research method, the study collects and analyzes data from books, scientific journals, and relevant documents discussing zakat and waqf within the context of Islamic economics. The findings indicate that zakat, through its direct redistribution of wealth, helps increase the purchasing power of the underprivileged and reduce income inequality, while waqf, especially in its productive form, supports the development of public infrastructure and social facilities. Both instruments, when managed professionally and transparently, can serve as complementary tools for fiscal and monetary policy, enhancing economic resilience and inclusivity. The synergy between zakat and waqf not only addresses immediate social needs but also contributes to long-term economic growth by empowering micro, small, and medium enterprises (MSMEs) and investing in education and health sectors. However, the study also highlights the need for further empirical research to measure the direct impact of zakat and waqf on national monetary stability. In conclusion, optimizing the management of zakat and waqf in accordance with Islamic principles can significantly strengthen the foundation of a just and sustainable economic system in Indonesia.